Extent and persistence of photic zone euxinia in Middle–Late Devonian seas – Insights from the Canning Basin and implications for petroleum source rock formation - Spaak, G.; Edwards, D.; Allen, H.; Grotheer, H.; Summons, R.; Coolen, Marco; Grice, Kliti (Elsevier, 2018)
Late Devonian mass extinctions attributed to extensive anoxia and/or euxinia of the oceans are associated with widespread deposition of organic-rich shales. Also in the epeiric waters of the Canning Basin (Western Australia), photic zone euxinia (PZE) prevailed during the Givetian–Frasnian, with geochemical evidence for PZE on the northern (Lennard Shelf)– and southern (Barbwire Terrace) margins of the Fitzroy Trough. On the Lennard Shelf, shales record episodic pulses of PZE associated with high algal activity due to enhanced nutrient supply, whereas a restricted marine setting on the Barbwire Terrace is thought to be the main driver for the development of persistent PZE and associated bacterial predominance. Structural evidence indicates that the Fitzroy Trough was a confined basin during the Late Devonian with the possibility of limited ocean circulation. Widespread PZE is expected to have developed in the poorly mixed water column, if the basin received sufficient nutrient supply for enhanced primary production. Notwithstanding the presence of anoxia during deposition of potential source rocks, only two small Devonian-sourced oil fields and numerous oil shows have been found in the Canning Basin. Biomarker assemblages show that the oils produced from the Lennard Shelf fields (i.e. Blina-1, Blina-4 and Janpam North-1) have substantially different molecular compositions to the minor oil recovered from Mirbelia-1 on the Barbwire Terrace. A correlation was established between the Lennard Shelf oils and rock extracts from the Gogo Formation at Blina-1 and McWhae Ridge-1 based on their hopane, sterane and carotenoids abundances. A definitive source correlation was not obtained for the Mirbelia-1 oil, but it did show some genetic affinity to the Givetian–Frasnian extracts from the Barbwire Terrace, suggesting that local source rocks are developed in the region.